Broad individual immersion-scattering of respiratory compliance likely substantiates dissimilar breathing mechanics - Olivier Castagna (Nature Portfolio, 2021)
Abstract Head-out water immersion alters respiratory compliance which underpins defining pressure at a “Lung centroid” and the breathing “Static Lung Load”. In diving medicine as in designing dive-breathing devices a single value of lung centroid pressure is presumed as everyone’s standard. On the contrary, we considered that immersed respiratory compliance is disparate among a homogenous adult group (young, healthy, sporty). We wanted to substantiate this ample scattering for two reasons: (i) it may question the European standard used in designing dive-breathing devices; (ii) it may contribute to understand the diverse individual figures of immersed work of breathing. Resting spirometric measurements of lung volumes and the pressure–volume curve of the respiratory system were assessed for 18 subjects in two body positions (upright Up, and supine Sup). Measurements were taken in air (Air) and with subjects immersed up to the sternal notch (Imm). Compliance of the respiratory system (Crs) was calculated from pressure–volume curves for each condition. A median 60.45% reduction in Crs was recorded between Up-Air and Up-Imm (1.68 vs 0.66 L/kPa), with individual reductions ranging from 16.8 to 82.7%. We hypothesize that the previously disregarded scattering of immersion-reduced respiratory compliance might participate to substantial differences in immersed work of breathing.